Primary vascular dysregulation syndrome: Possible implications for inner ear acute diseases?. Issue 5 (November 2015) - Pirodda, Antonio; Brandolini, Cristina; Cassandro, Ettore; Borghi, Claudio
Abstract: Primary vascular dysregulation syndrome has been reported as a possible cause for different eye diseases. Signs or symptoms of this syndrome not only may consist in a series of ocular disorders, as they possibly concern or are associated to various systemic conditions; even the damage of another terminal sensory organ as the inner ear is reported among the possible associations. Herein, the analogies between eye and inner ear are outlined, analyzing the PVD profile that well corresponds to our widely described model of subject without organic cardiovascular impairment but prone to inner ear acute disturbances. Actually, in absence of a recognized cause the latter can be due to a systemic dysregulation like the described one concerning ocular disorders.